Synthesis and characterization of novel activated carbon from Medlar seed for chromium removal: Experimental analysis and modeling with artificial neural network and support vector regression; Resource-Efficient Technologies; Vol. 3, iss. 3 - Solgi M. Mostafa; Tahereh N. Najibb; Ahmadnejadc S. Shahyar; Nasernejadb B. Bahram (2017, 2017)
Title screen